Quantification of IGF‐1 receptor is useful in the differential diagnosis of essential thrombocytosis from reactive thrombocytosis. (30th September 2019) - Wang, Jen C.; Shi, Guanfang; Wong, Ching; Gotlieb, Vladimir; Ramachandran, Preethi; Chen, Hui
Abstract: Background: To make a definite diagnosis of essential thrombocytosis (ET) from reactive thrombocytosis (RT), the most reliable criteria are the presence of driver mutations, namely JAK2, CALR, or MPL gene mutations. In the absence of these driver mutations, so‐called triple‐negative ET, the differential diagnosis could be difficult. Although bone marrow biopsy could be helpful, it may be difficult in some cases, to do gene sequence analysis to identify other clonal marker gene mutations than the driver mutations, as only very few were found. Methods: IGF‐1R quantification by flow cytometry in mononuclear cells (MNC) from peripheral blood was performed in 33 patients with ET (untreated or off treatment with hydroxyurea), 28 patients with RT, and 16 normal volunteer controls. Results: We found IGF‐1R levels were significantly elevated in ET patients compared to RT patients or controls. A cutoff value of 253 was chosen from the logistic regression to predict each patient's group, a value ≥253 meant that a patient belonged to the ET group (sensitivity 96.4% and specificity 68.6%). Conclusion: We suggest that adding quantification of IGF‐1R in blood MNC by flow cytometry is useful in differentiating ET from RT.